GPS Navigation Control for Autonomous Vehicle - Zulkifli, Husin; Mohd Najmuddin, Mohd. Hassan (Malaysian Invention and Design Society (MINDS), 2010)
En. Zulkifli Husin and his team from School of Computer & Communication Engineering won bronze for GPS Navigation Control for Autonomous Vehicle. ITEX 2007, 18th - 20th May 2007 was held at Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur.